Analyzing Profitability Determinants in Indonesian Conventional and Islamic Banking - Setiawan, Chandra; Ramadhita, Salsabila (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This article investigates the impact of financial ratios and macroeconomics on the profitability of conventional and Islamic banks in Indonesia. The study uses financial ratios as internal variables represented by CAR (X1), NPL/NPF (X2), and LDR/FDR (X3), while macroeconomics as an external variable is represented by BI7DRR (X4). The sample design used in this study includes conventional and Islamic banks from BUKU 1 and BUKU 2 in Indonesia, utilizing EViews and SPSS as analysis tools to test the proposed hypotheses. The analysis results show that CAR, NPL, and LDR have significant impacts on the ROA of conventional banks, while BI7DRR does not have a significant effect. On the other hand, in Islamic banks, only CAR and FDR significantly influence ROA, while NPF and BI7DRR do not have significant impacts. A paired sample t-test indicates a significant difference between the profitability (ROA) of conventional and Islamic banks. Based on these findings, it is recommended that conventional banks improve their management of CAR, NPL, and LDR, while Islamic banks need to focus on managing CAR and FDR, and develop innovative Sharia-compliant investment products to attract more stable funds.